If y(x) is the solution of the different equation y=e Where y(1)=e |
|||

(a) |
y(x) is decreasing in(0, 1) |
(b) |
y(x) is decreasing in |

(c) |
y(log |
(d) |
y (log |

If y(x) is the solution of the different equation y=e Where y(1)=e |
|||

(a) |
y(x) is decreasing in(0, 1) |
(b) |
y(x) is decreasing in |

(c) |
y(log |
(d) |
y (log |

1 Answer - 5876 Votes

3537

=e^{−2x}

I.F=e^{2x}+^{nx}=e^{2x}.x

So, y(xe^{2x})=^{2x}+c

⇒xye^{2x}= dx+c

⇒2xye^{2x}=x^{2}+2c

It passes throughwe get c=0

y=

⇒ (−2x+1)

⇒f(x)is decreasing in

y(log_{e}2)=

=log_{e}2